(untitled) (Update Dental College Journal, 2013)
Objectives: The objective is to draw attention to the anatomical variation of mandibular canal (double mandibular canals). Methods: This case report showing clinical and radiographic findings of a patient who was presented with bilateral double mandibular canals were recorded. Results: Bifid or double mandibular canals can be detected on a panoramic radiograph. More precise information about the course of the canal can be revealed on CBCT scan. Conclusions: The detection of these bifid or double mandibular canals are important because of their clinical implications. Special attention has to be made in the surgical procedures, especially involving the lower jaw. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13958 Update Dent. Coll. j: 2012; 2 (1): 31-34